Endoscopy provision: meeting the challenges. Issue 2 (10th February 2017) - Seward, Edward; Lumley, Sophie
Abstract : Background: Endoscopy activity has been increasing in the UK for many years. However, the increasing demand is currently disproportionate to delivered capacity. This, in combination with mandatory efficiency savings, presents an ongoing challenge in the effective continued delivery of diagnostic endoscopy services. Recent developments: New initiatives in the field of endoscopy that may impact on resource include: faecal immunochemical test, straight to test referral systems, nurse endoscopists, home enemas and split dose bowel preparation. Future potential: System review and improvement is paramount to ensure the diagnostic pathway is of a high clinical quality, efficient, patient focused and sustainable.